Usage and Understanding of Archaisms in King James Bible among Clergy and Laity in Ijebu-Ode, Nigeria - Amore, Kehinde Pedro; Soretire, Abiodun John; Ojelabi, Isaac Kehinde (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study was a survey of usage and understanding of archaisms of personal pronouns and verb endings in the King James Bible among the clergy and laity of selected churches within Ijebu-Ode metropolis of Ogun State, Nigeria. The study adopted the survey method with a sample size of 40 respondents selected via simple random sampling technique and 10 recorded homilies/liturgies from the selected churches cutting across the two major denominational blocs (Pentecostal and Protestant) using the King James Bible within Ijebu-Ode metropolis. Questionnaire was the main instrument used to obtain relevant information from the respondents who cut across various demographic groupings. Transcription served as the supporting instrument to gather pertinent data from the recorded homilies/liturgies. Thereafter, the descriptive method was employed in analysing the data gathered. The findings of the study enunciated the fact that archaisms of the King James Bible are still being used in churches through different platforms but majority of congregants lacked the proper understanding of the lexico-semantic and grammatical values of these archaisms. It is then recommended that clergymen should engage in thorough investigation into the KJV archaisms and the advantages they offer and educate their people accordingly, among other recommendations.